2016
DOI: 10.1016/j.bbrep.2015.11.015
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal gait, reduced locomotor activity and impaired motor coordination in Dgcr2 -deficient mice

Abstract: It has been suggested that the DGCR2 gene plays a role in the pathogenesis of 22q11.2 deletion syndrome. To analyze its function, we used our Dgcr2-knock-out/EGFP-knock-in mice (Dgcr2-KO mice). At 20-26 weeks of age, approximately 20% of Dgcr2-KO mice showed gait abnormalities with trembling and difficulty in balancing. Footprint test revealed awkward movements in Dgcr2-KO mice soon after they were placed on the floor. Once they started walking, their stride lengths were not different from wild-type mice. In s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Recent studies support a role for Dgcr2 in cortical projection neuron migration and differentiation, apparently as part of a complex that regulates Reelin-dependent phosphorylation of Dab1, Akt, Erk1/2 and subsequent signaling targets [135]. Dgcr2 deficient mice have gait abnormalities, reduced movement, and impaired motor coordination possibly due to loss of cerebellar Purkinje cells [136]. Finally, a DGCR2 missense mutation has been associated with non-syndromic SCZ [137], reinforcing a potential contribution to neural development or function.…”
Section: Main Textmentioning
confidence: 99%
“…Recent studies support a role for Dgcr2 in cortical projection neuron migration and differentiation, apparently as part of a complex that regulates Reelin-dependent phosphorylation of Dab1, Akt, Erk1/2 and subsequent signaling targets [135]. Dgcr2 deficient mice have gait abnormalities, reduced movement, and impaired motor coordination possibly due to loss of cerebellar Purkinje cells [136]. Finally, a DGCR2 missense mutation has been associated with non-syndromic SCZ [137], reinforcing a potential contribution to neural development or function.…”
Section: Main Textmentioning
confidence: 99%
“…Similar to as3mt , the human orthologue of this gene has been linked to schizophrenia [ 52 ]. Dgcr2 knock-out or knockdown mice show substantial locomotor deficits, altered neuronal migration and impaired Purkinje cell function [ 29 , 53 ]. We have previously suggested that Purkinje cell function may control zebrafish aggression [ 54 ] suggesting that this may represent an important node in a neural circuit that can control this behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…DGCR2 encodes an activity-dependent adhesion protein ( Kajiwara et al, 1996 ) and participates in neurodevelopment ( Maynard et al, 2003 ). Evidence indicated that abnormal behavior and locomotor activity were significantly reduced in DGCR2 knockout mice in open field tests ( Mugikura et al, 2016 ). Additionally, DGCR2 is associated with Schizophrenia ( Shifman et al, 2006 ; Xu et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%